ENVIRONMENTAL IMPACT REDUCTIONWITH THE APPLICATION OF THE INITIATIVE OF CLEANER PRODUCTION - PALMERI, Nivaldo; VENDRAMETTO, Oduvaldo; OLIVEIRA NETO, Geraldo Cardoso de (Revista Brasileira de Engenharia de Biossistemas, 2011)
The search for sustainability in the companies accounts a powerful ally the Cleaner Production (C+P). This action is emphasized in the world and Brazilian sector. This article enhances the concept application in a vehicle manufactureestablishing a sustainable plan applying the principles of cleaner production reducing the industrial residue and mitigating the final discharge. The program was carried out for reducing the use of wood and paper by the re-use and environmental savings.